Analisis Perbedaan Risiko Investasi Saham Sebelum dan Sesudah Akuisisi Perusahaan - Jenny Selvia; Indra Rinaldi; Hafizah Fauziah Hasibuan; Maria Agustia Laila; Jeni Sopianti; Yosep Eka Putra (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the differences in stock investment risk and the impact of the Debt-to-Asset Ratio (DAR), Debt-to-Equity Ratio (DER), Return on Assets (ROA), Return on Equity (ROE), and Current Ratio (CR) on companies listed on the Indonesia Stock Exchange (IDX) before and after acquisitions. This study sampled 10 companies. The method used was quantitative with a comparative approach. The results of data analysis conducted on 10 companies listed on the Indonesia Stock Exchange (IDX) by comparing annual financial statements before and after acquisitions for the periods 2024 and 2025 showed that, overall, this study confirms that in the short term, acquisitions tend not to have a direct beneficial impact on a company's financial performance or stock returns. This finding aligns with previous research findings, which indicate that the benefits of acquisitions are generally only felt in the medium to long term.